2014
DOI: 10.1007/s11482-014-9362-y
|View full text |Cite
|
Sign up to set email alerts
|

Collective and Individual Self-Esteem Mediate the Effect of Self-Construals on Subjective Well-Being of Undergraduate Students in China

Abstract: Human psychology and behavior are influenced by culture. Self-construals reflect the individualism-collectivism dimension at the level of individual personality. The current study aimed to explore how self-construals affect subjective well-being (SWB) in China, which has a collectivist culture. Chinese undergraduates (N=442) participated in this study. They responded to the self-construal scale, Rosenberg selfesteem scale, collective self-esteem scale and measures of SWB. The results suggested that the type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…This four-type self-construal model has since been used in a variety of contexts including conversational settings (Kim et al, 1996), dating relationships (Yum, 2004), socioemotional development among Vietnamese-American adolescents (Lam, 2006), and the impact of collective and individual self-esteem on subjective well-being among Chinese college students (Yu et al, 2014). These studies have indicated that possessing a bicultural identity influences individuals’ adjustment, cognition, and behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This four-type self-construal model has since been used in a variety of contexts including conversational settings (Kim et al, 1996), dating relationships (Yum, 2004), socioemotional development among Vietnamese-American adolescents (Lam, 2006), and the impact of collective and individual self-esteem on subjective well-being among Chinese college students (Yu et al, 2014). These studies have indicated that possessing a bicultural identity influences individuals’ adjustment, cognition, and behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To minimize the magnification of measurement error for latent variables, researchers have argued that item parcels should be created to act as indicators of variables with no sub-scales (Rogers and Schmitt, 2004). This can improve the reliability and normality of measurement (Yu et al, 2016). Therefore, two-item parcels were developed for PCB.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies have confirmed that the quality of neighborhood relationship is unrelated to the SWB of the elderly (Greenfield and Reyes, 2014; Reyes, 2014). This controversy may be due to the social and cultural differences between China and Western countries (Ram, 2010; Steele and Lynch, 2013; Yu et al, 2016). In Western countries, individual factors, such as personal achievement, self-concept, and self-evaluation, are considered relevant aspects of SWB (Kitayama and Markus, 2000; Lu and Gilmour, 2004).…”
Section: Discussionmentioning
confidence: 99%